Seismic vulnerability assessment of the old city centre of Seixal, Portugal - Ferreira, T. (2013)
The seismic vulnerability assessment of old traditional masonry building stocks, in a seismic risk mitigation perspective, is truly essential not only for buildings with recognized historical and patrimonial value, but also, in relation to regular buildings. In this sense, this paper approaches the issue of the seismic vulnerability assessment of masonry buildings through the application of a simplified methodology to building stock of the old city centre of Seixal, Portugal. This methodology is based on a vulnerability index, suitable in the evaluation of damage and in the creation of large scale loss scenarios (economical and human). Over 500 buildings were evaluated in accordance with the referred methodology and the results obtained were then integrated into a Geographical Information System tool. The integration of this kind of vulnerability and loss results into a GIS tool allows that city councils or regional authorities make their decisions based on a global view of the site under analysis, which led to more accurate and faster decisions either in terms of risk mitigation strategies or rehabilitation plans. This tool can also assumes great importance in the construction of safety and rescue plans.